Effects of climate change and sea-level rise on coastal habitat: Vulnerability assessment, adaptation strategies and policy recommendations. (15th March 2023) - Roy, Paramita; Pal, Subodh Chandra; Chakrabortty, Rabin; Chowdhuri, Indrajit; Saha, Asish; Shit, Manisa
Abstract: On a first-order basis, the global "sea level rise" induced by climate change magnifies coastal land subsidence. Various research related to this discipline is associated with estimated sea level vulnerability in various spatial scales. But the potential impact of climate change on sea level rise and its amalgamated vulnerability to the species remain undiscovered with appropriate procedures. So, in this perspective, our main objective of this research is to estimate the potential impact of climate change on sea level rise and it is associated with vulnerability to coastal habitat. From this research, it is established that the increasing tendency of sea level from the base period to the projected period. The major port city of India has been considered in this research. The qualitative "coastal vulnerability index (CVI)" is based on quantitative estimates to characterize the physical setting, including "geomorphology (G), sea level change (SLC), coastal slope (CS), relative sea-level change (RSLC), mean wave height (MWH), mean tide range (MTR), shoreline change rate (SCR), land use and human activities (LU), and population (P)". The projected sea level rise (SLR) is increasing at the highest rate under the higher RCP (Representative Concentrations Pathways) scenario. This information is very helpful to the decision maker for considering the most appropriate development strategies to maintain the sustainable development of coastal ecology in India. Graphical abstract: Image 1 Highlights: Sea level rise in changing climate has been estimated. Different RCP scenario in the projected period was considered. Sea level rise and associated vulnerability to coastal habitat has been estimated. There is an increasing tendency of sea level from the base period. Projected sea level rise is increasing, with higher RCP scenario.